2008
DOI: 10.1021/ac8008548
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Analysis of G Protein-Coupled Receptor by Mass Spectrometry: Identification of a Phosphorylation Site in V2 Vasopressin Receptor

Abstract: Phosphorylation plays vital roles in the regulation and function of the V2 vasopressin receptor (V2R), a G protein-coupled receptor (GPCR) that is responsible for maintaining water homeostasis in the kidney. Through a combination of immunoaffinity purification, immobilized metal affinity chromatography and nanoflow liquid chromatography tandem mass spectrometry, we identified a novel phosphorylation site (Ser 255 ) in the third intracellular loop of human V2R. We showed that the third intracellular loop could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Both parent proteins are G protein-coupled receptors (GPCR) in which the phosphorylation patterns in the selected regions play a key role in activity and binding. [20,34] To achieve optimal temperature control during the synthesis of the model HPPs, the synthesis was performed on the Figure 1. Methods for the synthesis of multi phosphorylated peptide (MPPs).…”
Section: Resultsmentioning
confidence: 99%
“…Both parent proteins are G protein-coupled receptors (GPCR) in which the phosphorylation patterns in the selected regions play a key role in activity and binding. [20,34] To achieve optimal temperature control during the synthesis of the model HPPs, the synthesis was performed on the Figure 1. Methods for the synthesis of multi phosphorylated peptide (MPPs).…”
Section: Resultsmentioning
confidence: 99%
“…Sixth , phosphorylation plays a pivotal role in the regulation of GPCR function. Previous studies identified putative sites which are clustered in the C terminus and in ICL3 and are phosphorylated by specific GPCR kinases (GRK) and by protein kinase A (PKA), respectively [41] [43] . Whereas abundant putative Ser/Thr phosphorylation sites are found in the C terminus of all V2R orthologs the putative PKA phosphorylation site within ICL3 at Ser 255 [41] is substituted by Asn, Gly and Asp in many V2R orthologs implicating that this position is, if at all, a substrate for PKA in only a few species.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas site-directed mutagenesis was considered the primary method for identifying the potential phosphorylation residues in early studies, multiple novel techniques have been ND (Wu et al, 2008) CHO, Chinese hamster ovary cells; CK2, casein kinase II; COS7, derived from CV-1 in origin with SV40 genes monkey kidney cells; CPM, chymotryptic phospho-peptide mapping; HEK293, human embryonic kidney 293 cells;…”
Section: Phosphorylation Of the Gpcr At Multiple Sitesmentioning
confidence: 99%